2017
DOI: 10.1021/acs.biomac.7b00344
|View full text |Cite
|
Sign up to set email alerts
|

Gene Transfection Mediated by Catiomers Requires Free Highly Charged Polymer Chains To Overcome Intracellular Barriers

Abstract: The prospective use of the block copolymers poly(ethylene oxide)-b-poly[2-(diethylamino)ethyl methacrylate] (PEO-b-PDEA) and poly[oligo(ethylene glycol)methyl ether methacrylate]-b-poly[oligo(ethylene glycol)methyl ether methacrylate-co-2-(diethylamino)ethyl methacrylate-co-2-(diisopropylamino)ethyl methacrylate] (POEGMA-b-P(OEGMA-co-DEA-co-DPA)) as nonviral gene vectors was evaluated. The polymers are able to properly condense DNA into nanosized particles (R ≈ 75 nm), which are marginally cytotoxic and can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 41 publications
2
15
0
Order By: Relevance
“…However, for DEAE-CH 50 nanoparticles, the presence of excess polycations did not affect the efficiency. On the contrary, at an N/P ratio of 10, the best silencing was achieved, agreeing with previous reports by other groups that indicated that an excess of free or weakly-associated polycation chains can improve the lysosomal release [12,13].…”
Section: In Vitro Transfection Efficiencysupporting
confidence: 92%
See 1 more Smart Citation
“…However, for DEAE-CH 50 nanoparticles, the presence of excess polycations did not affect the efficiency. On the contrary, at an N/P ratio of 10, the best silencing was achieved, agreeing with previous reports by other groups that indicated that an excess of free or weakly-associated polycation chains can improve the lysosomal release [12,13].…”
Section: In Vitro Transfection Efficiencysupporting
confidence: 92%
“…nanoparticles encapsulating siRNA prepared with chitosan 470 kDa, in the presence of polyguluronate mediated silencing efficiencies near 50% with HEK 293FT and HeLa cells [10]. However, transfection efficiencies of low Mw chitosan nanoparticles may be adjusted by increasing the amino to phosphate N/P ratios and recent studies have indicated that an excess of free or weakly associated polycation chains plays an important role on the uptake process and transfection efficiency [11][12][13]. Chitosans having low and high Mws, (2 kDa to 500 kDa) are used in large charge excess to siRNA, and N/P ratios in the range of 10 to 200 are commonly found in the literature [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The respective flow cytometry dot plots are given in the Supporting Information (Figures S5 and S6, Supporting Information). Indeed, the obtained values are consistent with a recent study we conducted . The cellular uptake, subcellular localization, and gene expression of the BPEI and BPEI‐Lac polyplexes were finally examined qualitatively via fluorescence microscopy.…”
Section: Resultssupporting
confidence: 87%
“…It has more recently be shown that free polymer chains can have an impact gene transfection. [51][52][53] Whereby the mechanism of cationic polymer mediated plasmid transfection, could be explained by free polymer interaction with the interior endosomal membrane and creation of pores, allowing an amount of polyplex into the cytoplasm. Any small change in the transfection process could have disproportionate effect on observed expression due to endosome escape being very inefficient.…”
Section: Effect Of Polymer Architecture On Toxicity and Pdna Transfecmentioning
confidence: 99%